Caṅka ilakkiyattil nāṭṭuppur̲a marapukaḷ (Kāvyā, 2012)
Study on the folklore in Sangam literature
Includes bibliographical references (pages 90-91). - Tamil in Tamil-Schr
Keywords: Sangam literature; Folklore in literature